Empleo potencial de pgpr solubilizadores de minerales y productoras de fitohormonas en el cultivo de arroz (Oryza sativa L.). - Manzo Campos, Teresa De Jesús (2022)
The use of new strains, with halophilic properties that have a suppressive effect against the affections that rice cultivation presents in ferric soils, in order to facilitate greater absorption and use of the mineral. The objective of the research is to evaluate the potential of PGPR solubilizers of minerals and producers of phytohormones in the cultivation of rice